Effective practice instructional strategies: Design of an instrument to assess teachers' perception of implementation. (March 2018) - Ford, Catherine
Highlights: The instrument yielded a S/CVI = 0.72 and a reliability score of 0.73. The MEPISA was created using a 4 phrase instrument development process. The instrument assesses perceived effective practice implementation of teachers. Abstract: The purpose of this research was to explore teacher implementation of effective practice instructional strategies. This included the creation of an instrument that can be used to assess how secondary teachers in the core content areas (English, math, science, social studies) in Minnesota, US, perceive implementation of effective practice instructional strategies. This instrument, The Minnesota Effective Practice Instructional Strategies Assessment (MEPISA), was developed using a four-step instrument development process, which included content domains, question creation, a review by a panel of experts, and a pilot. The MEPISA yielded a S/CVI = 0.72 and a reliability score of 0.73. This instrument may contribute to mitigating the theory-practice gap in the effective practice of instructional strategies and can provide insight into how teachers perceive the frequency in which they use instruction strategies when considering demographic data.